Insecticide with the active ingredient methomyl interferes with the growth and survival of the jatiumbulan tilapia strain (Oreochromis niloticus) - Diana Arfiati; Sri Andayani; Afella Osa; Vina Nur Nadiro; Nurhalisa Nurhalisa (Jurnal Penelitian Pendidikan IPA, 2023)
Insecticides with the active ingredient methomyl are a class of pesticides used to protect agricultural crops from attack by pests such as insects. The areas that used this insecticide were from the results of previous studies, namely the Musi Rawas Paddy Field Center in South Sumatra and Ngantru District, Tulungagung Regency. However, it is possible that many other areas use it. This study aims to prove that the insecticide with the active ingredient metomyl interferes with the growth and survival of the Jatiumbulan tilapia strain (O. niloticus). The treatment consisted of a control and three exposure concentrations namely 1.8, 4.015 and 6.2 mg/L with 3 repetitions each. Exposure was carried out artificially once in rearing water and observations were made for 4 days (96 hours). In conclusion, the results showed that as the exposure concentration of the insecticide with the active ingredient metomil (Lannate with 25 % methomyl) increased, the stress occurred faster which resulted in decreased growth, survival, time of death, and clinical symptoms. However, the concentration of 6.2 mg/L (treatment C) gave significantly different results in survival parameters compared to the 1.8 and 4.015 mg/L treatment. This is because in treatment C there was stress to death and this condition did not occur in treatment A and B